2010
DOI: 10.1016/j.jbiomech.2009.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Geometry, time-dependent and failure properties of human meniscal attachments

Abstract: Meniscectomies have been shown to lead to osteoarthritis and the success of meniscal replacements remains questionable. It has been suggested that the success of a meniscal replacement is dependent on several factors, one of which is the secure fixation and firm attachment of the replacement to the tibial plateau at the horn locations. To aid in the development of meniscal replacements, the objectives of the current study were to determine the time-dependent and failure properties of human meniscal attachments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
3
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 43 publications
6
71
3
5
Order By: Relevance
“…In the 2 previous studies noted. 9,18 the authors did not control for age or sex with their specimens, which may explain, at least in part, the differences between the 2 studies. Interestingly, differences in ultimate failure strengths between the 4 roots may be related to mobility differences within the menisci themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2 previous studies noted. 9,18 the authors did not control for age or sex with their specimens, which may explain, at least in part, the differences between the 2 studies. Interestingly, differences in ultimate failure strengths between the 4 roots may be related to mobility differences within the menisci themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Hauch et al 9 were the first to compare the stiffness of the meniscal roots. Just as in our study, they reported the highest stiffness for the AL root (219 N); however, they reported that the PL root had the lowest stiffness (130 N), 9 as compared with the PM root in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nach Messung der Querschnittsfläche konnten sie den Elastizitätsmodul der Bänder bestimmen, welcher zwischen 150 und 300 MPa betrug. Im Anschluss an diese Arbeit wurden dieselben Versuche an humanen Verankerungsligamenten vorgenommen [8]. Dabei wurden signifikante Unterschiede zwischen den anterioren und posterioren, sowie den lateralen und medialen Bändern aufgezeigt.…”
Section: Hintergrundunclassified
“…Tab. 3; [6,8,21,25]). Es scheint, dass die mechanische Kompetenz der Bänder mit ihrem geometrischen Querschnitt korreliert, was bisher jedoch in der Literatur noch nicht bestätigt werden konnte.…”
Section: Diskussionunclassified
“…The spring used was type "SPRINGA" which strictly uses the change in length in the spring between the initial and deformed configurations to determine the spring displacement. The stiffness's of the springs used in each attachment horn were taking from published data of the attachment horn's stiffness [87], shown in Table 7. The rest of the nodes on the meniscal attachment face were tied to the central node using a kinematic coupling constraint.…”
Section: Meniscal Attachment Constraintsmentioning
confidence: 99%